Correlation of manufacturing defects and impact behaviors of kenaf fiber reinforced hybrid fiberglass/Kevlar polyester composite - Mat Jusoh, Suriani; Salit, Mohd Sapuan; Ghazali, Che Mohd Ruzaidi; Jesuarockiam, Naveen; H., Syukriyah; M., Ziefarina (Industrial Chemistry Research Institute, 2021)
In this study, the impact properties of kenaf fibre reinforced hybrid fiberglass/Kevlar polymeric composite was investigated. In this study, a new fiber arrangement based on kenaf bast fiber as reinforcement to the hybrid fiberglass/Kevlar fiber and polyester as matrix used to fabricate the hybrid polymeric composite. Five different types of samples with different of kenaf fiber content based on volume fraction (0, 15, 45, 60 and 75%) to hybrid fiberglass/Kevlar polymer composites were manufactured. 0% of kenaf fiber has been used as control sample. The results showed that hybridization has improved the impact properties. These results were further supported through SEM micrograph of the manufacturing defects of the polymer composite. Based on literature work, manufacturing defects that occurs in composite system reduced the mechanical properties of the material. Therefore, in this research the correlation of impact behaviors and manufacturing defects of kenaf fiber reinforced hybrid fiberglass/Kevlar polymeric composite has been successfully done. As conclusion, the highest manufacturing defects determined in the composites during the fabrication significantly lowest the results of impact behavior.